Epidemiological investigation reveals local transmission of SARS-CoV-2 lineage P.1 in Southern Brazil - Salvato, Richard Steiner (2021)
Since its detection in December of 2020, the SARS-CoV2 lineage P.1, descendent of B.1.1.28 lineage, has been identified in several places in Brazil and abroad. This Variant of Concern was considered highly prevalent in Northern Brazil and now is rapidly widening its geographical range. Here, we present epidemiological and genomic information of the first case of P1 lineage in Rio Grande do Sul state, in a patient with no reported travel history and a tracked transmission chain. These findings occurred in a tourist destination representing an important hub receiving tourists from diverse places.